Dexmedetomidine Ameliorate CLP-Induced Rat Intestinal Injury via Inhibition of Inflammation. (26th July 2015) - Chen, Yanqing; Miao, Liyan; Yao, Yusheng; Wu, Weilan; Wu, Xiaodan; Gong, Cansheng; Qiu, Liangcheng; Chen, Jianping
Abstract : The aim was to verify that dexmedetomidine (DEX) can attenuate CLP-induced intestinal injury via inhibition of inflammation. Male Sprague-Dawley (SD) rats were randomly allocated into Sham group and the other three CLP model groups, in terms of different treatments: placebo, DEX, and yohimbine plus DEX (DEX + YOH) groups. Pathology examination was conducted with HE stain. To identify differences among groups, the levels of DAO, and D-lactate in serum were measured by spectrophotometry, and the levels of TNF- α, IL-1 β, and IL-6 in serum and organ were measured by ELISA. The expressions of occludin and TLR4 in tissue were detected by Western blot. The survival rate of an additional group of animals within 7 d was recorded. In DEX group, mortality was lower, histology change was minor, DAO, and D-lactate levels were reduced, and occludin expression was increased; the expressions of TNF- α, IL-1 β, IL-6, and TLR4 were also decreased in DEX group. These results indicated that acute intestinal injury induced by CLP was mitigated by DEX treatment. However, these effects of DEX were significantly attenuated by yohimbine in DEX + YOH group. Our study indicated the protective effects of DEX on CLP-induced injury, which may be associated with the inhibition of inflammation via modulating TLR4 pathway and can be blocked by yohimbine.